2022
DOI: 10.1108/rbf-03-2022-0090
|View full text |Cite
|
Sign up to set email alerts
|

The association between financial literacy confidence and financial satisfaction

Abstract: PurposeThis study examines the association between financial literacy confidence and financial satisfaction. The authors posit that overconfident poor performers will experience greater levels of financial satisfaction and underconfident high performers will experience lower levels of financial satisfaction.Design/methodology/approachBased on the results of an objective financial literacy assessment and a subjective financial literacy assessment, variables measuring study participants' financial literacy overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Jappelli and Padula (2015) suggest that solid financial knowledge supports reducing the costs of entering stock markets. Pearson and Korankye (2022) reported that financial literacy overconfidence is positively related to increased levels of financial satisfaction and vice-versa. Bourova et al (2018) investigated the financial literacy levels and the intensity of financial hardship among Australians with debt problems.…”
Section: Moderating Role Of Financial Confidencementioning
confidence: 99%
“…Jappelli and Padula (2015) suggest that solid financial knowledge supports reducing the costs of entering stock markets. Pearson and Korankye (2022) reported that financial literacy overconfidence is positively related to increased levels of financial satisfaction and vice-versa. Bourova et al (2018) investigated the financial literacy levels and the intensity of financial hardship among Australians with debt problems.…”
Section: Moderating Role Of Financial Confidencementioning
confidence: 99%
“…Financial knowledge. Financial knowledge, representing both subjective and objective knowledge, is an essential factor that is known to influence financial behavior (Korankye et al, 2023;Pearson and Korankye, 2022). First, subjective financial knowledge represents people's confidence in their knowledge of financial matters (Rosen and Sade, 2019).…”
Section: Student Loan Debt In Retirementmentioning
confidence: 99%
“…This finding points to the significance of financial selfefficacy to financial satisfaction and justifies support the inclusion of financial self-efficacy as a predictor of financial satisfaction in this current study, which explores the relationship between affect, financial self-efficacy, and financial satisfaction then increase their perception of their financial situation and well-being. In summary, the existing literature has focused on the influence of economic and socio-demographic factors on financial satisfaction (Aboagye & Jung, 2018;Pearson & Korankye, 2022;Seay et al, 2015). More recently, there is a growing body of literature on how psychosocial factors relate to financial satisfaction (Davis & Runyan, 2016;Tharp, Seay, Carswell, et al, 2020;Tharp, Seay, Stueve, et al, 2020).…”
Section: Emotions Financial Self-efficacy and Financial Satisfactionmentioning
confidence: 99%
“…In summary, the existing literature has focused on the influence of economic and socio‐demographic factors on financial satisfaction (Aboagye & Jung, 2018; Pearson & Korankye, 2022; Seay et al, 2015). More recently, there is a growing body of literature on how psychosocial factors relate to financial satisfaction (Davis & Runyan, 2016; Tharp, Seay, Carswell, et al, 2020; Tharp, Seay, Stueve, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%